Problem Solving Process of AKM Algebra Content in Junior High School Students Reviewed from Extrovert and Introvert Personality Types - Dewi Purnamasari; Ismail (Universitas Negeri Surabaya, 2024)
This study aims to describe the problem-solving process of AKM algebra content in junior high school students with extrovert and introvert personality types. This study is a descriptive-qualitative study conducted in class VIII of junior high schools in Sidoarjo Regency. The subjects in this study consisted of 2 students with equal mathematical abilities, namely 1 extrovert student and 1 introvert student. The research instruments were in the form of MBTI personality type questionnaires, TPM AKM questions, and interview guidelines. Data analysis techniques were carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study showed that the problem-solving process of AKM extrovert students in understanding problems was to use symbols and not write to state what was asked, while introvert students used symbols and wrote to state what was known and what was asked. In the step of making a plan, extrovert and introvert students can consider the strategies used in solving the problem. In the step of implementing the plan, extrovert and introvert students use the chosen strategy to solve the problem. In implementing the plan, introvert students check all steps repeatedly while extrovert students check only part of the steps. Then, in the review step, extroverted students only rechecked some of their solutions, while introverted students rechecked all of their solutions. Finally, the results of this study can provide information for teachers as consideration and input so that they can develop students' problem-solving processes during learning.